2015
DOI: 10.1111/bcp.12626
|View full text |Cite
|
Sign up to set email alerts
|

Time‐trends in the prescribing of gastroprotective agents to primary care patients initiating low‐dose aspirin or non‐steroidal anti‐inflammatory drugs: a population‐based cohort study

Abstract: AIMSLow-dose aspirin (LDA) and non-steroidal-anti-inflammatory drugs (NSAIDs) both increase the risk of upper gastrointestinal events (UGIEs). In the Netherlands, recommendations regarding the prescription of gastroprotective agents (GPAs) in LDA users were first issued in 2009 in the HARM-Wrestling consensus. National guidelines on gastroprotective strategies (GPSs) in NSAID users were issued in the first part of the preceding. The aim of the present study was to examine time-trends in GPSs in patients initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…A systematic review of preventable adverse drug events (pADEs) in ambulatory care found that gastrointestinal toxicity resulting from a failure to prescribe prophylactic agents with NSAIDs or antiplatelets was the most frequently identified adverse outcome in studies of pADEs requiring hospitalization [25]. A recent cohort study in a Netherlands primary care population found that adequate gastroprotection was absent in the majority of patients at high risk of experiencing a GI bleed [26]. The authors report that 52 % of those using NSAIDs and 68 % using low dose ASA were using them potentially inappropriately.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of preventable adverse drug events (pADEs) in ambulatory care found that gastrointestinal toxicity resulting from a failure to prescribe prophylactic agents with NSAIDs or antiplatelets was the most frequently identified adverse outcome in studies of pADEs requiring hospitalization [25]. A recent cohort study in a Netherlands primary care population found that adequate gastroprotection was absent in the majority of patients at high risk of experiencing a GI bleed [26]. The authors report that 52 % of those using NSAIDs and 68 % using low dose ASA were using them potentially inappropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown a consistent upward trend in PPI use, up to a 13-times increase in the 12 years up to 2006 in Australia. [18][19][20][21] A Dutch study found a rise in PPI prescribing in individuals in primary care initiated on low-dose aspirin or a NSAID from 2000 to 2012 at all levels of risk of upper GI bleeding. 21 Regarding trends in maximal dose prescribing, a growing prevalence of high-intensity PPI use was noted in a Canadian study.…”
Section: Findings In the Context Of Previous Researchmentioning
confidence: 99%
“…[18][19][20][21] A Dutch study found a rise in PPI prescribing in individuals in primary care initiated on low-dose aspirin or a NSAID from 2000 to 2012 at all levels of risk of upper GI bleeding. 21 Regarding trends in maximal dose prescribing, a growing prevalence of high-intensity PPI use was noted in a Canadian study. 22 Considering prescribing between 1997 and 2004 in this Canadian research, polypharmacy was associated with use of high doses, and older age was associated with lower odds, consistent with the current study.…”
Section: Findings In the Context Of Previous Researchmentioning
confidence: 99%
“…Proton pump inhibitor (PPI) therapy reduces the risk of aspirinassociated upper GI events and is recommended for patients at an increased risk [15,16]. However, several studies suggest that there are treatment gaps with the co-prescribed prophylactic PPI prescriptions and/or use [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Specifically, when PPIs are co-prescribed, adherence rates are often suboptimal, leaving patients at risk for adverse upper GI outcomes [27,28,32,33,35].…”
Section: Introductionmentioning
confidence: 99%